An Investigation of Soil Resistivity Level at UTHM Pagoh Campus - Hamsa, Haziqah; Mohamed Yusop, Fatimah; Kosnin, Hilmi (Progress in Engineering Application and Technology, 2023)
The most cost effective and time consuming method for achieving and maintaining the required earth resistance value during the installation of buried pipes lifespan is to be aware of the soil resistivity at the chosen location. Indirect measurements of soil parameters including moisture content, pH, resistance level, temperature, and soil texture may all be made using the indicator of soil resistivity. There are huge underground pipe networks used to convey water all over the world. To guarantee a secure and effective pipeline operation, corrosion-related surface defect and structural failure must be carefully avoided. Maintenance and pipe replacement are crucial components of an effective system because corrosion and leaks are frequent issues. Based on data from the Sime Darby Property Selatan Sdn. Bhd. (SDPS) shows that  the total amount of cases recorded was 9 cases which was involving buried pipes at UTHM Campus Pagoh area and the leakage was start from 2018 until now. With the aid of the Wenner Four Pin Method, a real-time soil resistivity measuring system has been used in this study. The data collected with this technique was used to determine the amount of soil resistivity that contributes to the corrosion of underground piping and the amount of electrical current that can pass through the ground. The purpose of this study was to measure the voltage and current for the different depth of soil using Wenner Four Pin Method and to categorize the soil type at chosen location. Despite the soil resistivity at the chosen location indicating a high resistivity level, which is typically associated with non-corrosive conditions, it is important to note that corrosion can still occur even in non-corrosive environments. This can be attributed to various factors that may contribute to localized corrosion phenomena.